Meiofauna community structure in the Senapelan River Pekanbaru - Saddam Husein; Nur El Fajri; Adriman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Senapelan River receives many types of pollutants originated from households and industries present around the river. The presence of the pollutant may decrease the water quality and affects the meiofauna community living in that river. A research aims to understand the water quality of the river based on meiofauna structure was conducted on June-July 2015. There were 3 stations and the meiofauna was sampled 3 times, once/ week. The types of meiofauna was then identified and the abundance, uniformity and dominancy index were calculated. Water quality parameters such as temperature, turbidity, depth, pH, dissolved oxygen, substrate type, and organic materials were measured. Result shown that there were 5 spesies (4 classes) of meiofauna. There were Oligochaeta (1 spesies), Polychaeta (1 spesies), Nematod (2 spesies) and Turbellaria (1 spesies). The abundance of the meiofauna was ranged from 39-1,337 organism/m2, the diversity index value (H’) was 1.39 – 2.04, the dominance index value (C’) was 0.27 – 0.42 and the equitability index value (E) was 0.70 – 9.91. These values indicate that the Senapelan River is slightly polluted, but it is able to support the live of specific meiofauna only.Keyword : Meiofauna, Bioindicator, Senapelan River